Micellar-enhanced ultrafiltration (MEUF) for removal of rhodamine B (RhB) from aqueous system. Issue 3 (28th February 2022) - Yusaf, Amnah; Usman, Muhammad; Mansha, Asim; Saeed, Muhammad; Ahmad, Matloob; Siddiq, Muhammad
Abstract: Micellar-enhanced ultrafiltration (MEUF) has proved itself to be a potentially attractive tool to remove contaminants from waste water. The reported study is particularly focused on the interaction and removal of cationic dye, Rhodamine B (RhB), using micellar solution of anionic surfactants, that is, Sodium dodecyl sulfate (SDS) and Sodium Oleate (SO). Dye removal efficiency has been assessed in terms of rejection percentage and permeate flux, using cellulose membrane of 10, 000 molecular weight cutoff (MWCO). The effects of various factors, that is, ionic strength, concentration of surfactants, concentration of electrolyte, pH, operating pressure and rotations per minute (RPM) has been observed. It has been concluded that the maximum rejection of dye has been observed using micellar media of SDS. Overall, it has been observed that the rejection coefficient of dye is higher at higher concentration of surfactants and electrolyte and at lower values of pH, RPM and transmembrane pressure. Graphical Abstract: UF0001